MONOPOLI DALAM ISLAM DARI KLASIK HINGGA KONTEMPORER - Safwan Safwan (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2017)
Islam has given many concessions to it’s adherents to run the business and it’s business in accordance, but in fact how many business people who perform acts that are actually strictly prohibited in Islamic sharia. Many excuses they propose to cover up their bad intentions. They are also aware that what they will do can harm others, but that is life in the world, the law of the jungle is still valid, who is strong then he will be happy in the world even if only temporarily, and who is weak then forever oppressed. Of the many fraudulent ways that can bring in profits doubled, monopoly is one of the commonly used modes, especially for large investors. This research is a qualitative research and includes literature study. This research shows that the difference of one's opinion about monopoly will determine how the law of monopoly and there are some elements of monopoly that is time constraints, chartering goods, human needs, multiple profit-making, and the absence of competitors or other suppliers, and the existence of hoarding activities. Keyword : Monopoly, Business Competation, Market, Business